2020
DOI: 10.1101/2020.09.18.303495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Belief states and categorical-choice biases determine reward-based learning under perceptual uncertainty

Abstract: In natural settings, learning and decision making often takes place under considerable perceptual uncertainty. Here we investigate the computational principles that govern reward-based learning and decision making under perceptual uncertainty about environmental states. Based on an integrated perceptual and economic decision-making task where unobservable states governed the reward contingencies, we analyzed behavioral data of 52 human participants. We formalized perceptual uncertainty with a belief state that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 59 publications
(96 reference statements)
3
21
0
Order By: Relevance
“…We showed that most participants were able to adapt successfully to all three types of uncertainty; they managed to learn the correct state-action mapping under expected state uncertainty (due to noisy visual inputs) and expected reward uncertainty (due to reward being generated from a probability distribution), and managed to adapt to the unexpected uncertainty due to a nonsignalled reversal in the state-action reward contingency. This is in line with previous work that looked at reward-based learning under expected reward uncertainty (Don et al, 2019), expected state uncertainty (Bruckner et al, 2020) and unexpected reward uncertainty (Brown & Steyvers, 2009). Surprisingly, participants collected more rewards in state uncertainty than in reward uncertainty, partly due to their higher exploration rate under the reward uncertainty condition.…”
Section: Summary Of the Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We showed that most participants were able to adapt successfully to all three types of uncertainty; they managed to learn the correct state-action mapping under expected state uncertainty (due to noisy visual inputs) and expected reward uncertainty (due to reward being generated from a probability distribution), and managed to adapt to the unexpected uncertainty due to a nonsignalled reversal in the state-action reward contingency. This is in line with previous work that looked at reward-based learning under expected reward uncertainty (Don et al, 2019), expected state uncertainty (Bruckner et al, 2020) and unexpected reward uncertainty (Brown & Steyvers, 2009). Surprisingly, participants collected more rewards in state uncertainty than in reward uncertainty, partly due to their higher exploration rate under the reward uncertainty condition.…”
Section: Summary Of the Resultssupporting
confidence: 91%
“…A more recent study showed that people use belief states when learning under state uncertainty, but their learning is modulated by categorical perceptual commitments (Bruckner et al, 2020). As in our experiment, participants had to learn state-response mappings via reward feedback under perceptual uncertainty.…”
Section: Relationship With Belief-state Based Learningmentioning
confidence: 90%
See 2 more Smart Citations
“…Our current results also only examined uncertainty about reward expectations. However, there exist several alternative measures of uncertainty such as confidence 71 , 72 , perceptual uncertainty 73 , 74 , and computational uncertainty induced by cognitive load 75 , all of which could influence exploration behavior in different ways. Thus, we expect future studies to increasingly focus on disentangling different sources of uncertainty and their effects on the exploration-exploitation dilemma.…”
Section: Discussionmentioning
confidence: 99%